Opening the black box of a failed drinking water project. The case of the Proyecto Integral de Agua Potable in the city of Pasco from the Actor-Network Theory - Aguilar, Pável (2022)
This research uses the Actor-Network Theory toolbox to open the black box behind the Pasco’s Proyecto Integral de Agua Potable Project collapse, an ambitious public infrastructural intervention caused by both local pollution conditions and the lack of water resources. We worked with a qualitative methodology focused on process tracing through the analysis of multi-sited narratives about humans and non-humans. Non-participant observation, documentary analysis, and anonymous semi-structured interviews with fourteen spokespersons of the project were used. The results suggest that the project collapse was caused by the fragility of the alliance system since the spokespersons were unable to centralize the management of the Local Implementation Network or translate the sociotechnical controversies around water, given its multidimensional nature.